Students' Motivation and Engagement in the Implementation of Individual Development Plan for Underrepresented Minority (URM) Students in Undergraduate STEM Training Programs - Nishika Edwards; Richard L. Goodwin; Mohammed K. Khalil; Lauren A. Fowler; Thomas Nathaniel (MDPI AG, 2024)
Despite recent progress, statistics show an urgent need for growth in the numbers of underrepresented minority (URM) students in STEM fields. An individual development plan (IDP) has been used to assist Ph.D. trainees in exploring career paths, developing short- and long-term career goals, and creating action plans to achieve these goals. The National Institutes of Health (NIH) and many institutions require the completion of the IDP by graduate students, postdoctoral researchers, and junior faculty mentees to enhance career development. However, little information exists regarding how motivated and behaviorally engaged undergraduate URM undergraduate students are in using IDP as a tool to develop their STEM career pathway. In this study, researchers present data from the motivation levels and behavioral engagement factors that are associated with the effectiveness of the IDP with 20 URM students recruited for the REP Summer program. A total of 85% of students strongly agreed that the IDP was most effective in assessing and reflecting on their academic and professional goals. The mentorship needs were met by 80% of the students, while 75% of the students agreed that the IDP was very effective in helping to identify short-term and long-term goals for their undergraduate studies. Moreover, 70% of the students were satisfied with the IDP in developing an action plan, identifying short-term and long-term goals for their professional careers, and assessing their scientific skills, interests, and values. URM students are intrinsically and extrinsically motivated to implement the IDP and pursue careers in STEM. Findings suggest that URM students' motivation and behavioral engagement levels impact the effectiveness of the implemented IDP with these students. There is a need to identify factors that enhance the effectiveness of the IDP to determine how to maximize the career development of URM students in STEM programs.